Effect of cationic molecules on the oxygen reduction reaction on fuel cell grade Pt/C (20 wt%) catalyst in potassium hydroxide (aq, 1 mol dm−3)1. Issue 18 (14th May 2015) - Ong, Ai Lien; Inglis, Kenneth K.; Whelligan, Daniel K.; Murphy, Sam; Varcoe, John R.
<x xml:space="preserve">Abstract</x> This study investigates the effect of a selection of small cationic molecules on the ex situ performance of a fuel cell grade oxygen reduction reaction catalyst (Johnson Matthey HiSPEC 3000) in aqueous KOH using rotating disk electrode voltammetry.